ANALISIS INDEKS KEPUASAN MASYARAKAT MAL PELAYANAN PUBLIK KOTA PROBOLINGGO - aprilia, melisa srimurty; Puspitarini, Renny Candradewi (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2021)
This study aims to describe the results of the analysis of the community satisfaction index in the Public Service Mall (MPP) in the City of Probolinggo. The community satisfaction index is a product of a community satisfaction survey whose guidelines can be found in the Regulation of the Minister of PAN-RB Number 14 of 2014. In it there are elements of assessment including conformity to service requirements, ease of service procedures, speed of service time, suitability of service products, competence of officers, behavior of officers, quality of facilities and infrastructure, handling of complaints on service use, and customer satisfaction. The existence of a community satisfaction survey is an effort to determine the quality of public services. For this reason, community satisfaction surveys need to be conducted periodically and the results must be published for the general public to know. This survey was conducted using data collection techniques by distributing questionnaires consisting of nine elements of questions that are loaded simply so that the pluralist respondents can easily understand them. The analysis was performed using descriptive quantitative data analysis. This study comes to the conclusion that the level of community satisfaction is quite good with public services at MPP. The procedures are easier and the staff at MPP are polite and friendly. However, there are still some shortcomings, for example a lack of resource facilities and also a special site for online complaints so that people can more easily provide opinions, suggestions, or criticisms of the services provided at MPP and this requires a further evaluation stage. Another recommendation is that the queue information system can be a solution to break down the congestion of public services at certain hours and certain days. In addition, through the queue information system, people with digital literacy can register, know and monitor queues online. Keywords: public service, customer satisfaction, public service mall, public satisfaction survey, public satisfaction index